Global raster dataset on historical coastline positions and shelf sea extents since the Last Glacial Maximum. Issue 11 (14th August 2022) - De Groeve, Johannes; Kusumoto, Buntarou; Koene, Erik; Kissling, W. Daniel; Seijmonsbergen, Arie C.; Hoeksema, Bert W.; Yasuhara, Moriaki; Norder, Sietze J.; Cahyarini, Sri Yudawati; van der Geer, Alexandra; Meijer, Hanneke J. M.; Kubota, Yasuhiro; et al.
Abstract: Motivation: Historical changes in sea level caused shifting coastlines that affected the distribution and evolution of marine and terrestrial biota. At the onset of the Last Glacial Maximum (LGM) 26 ka, sea levels were >130 m lower than at present, resulting in seaward‐shifted coastlines and shallow shelf seas, with emerging land bridges leading to the isolation of marine biota and the connection of land‐bridge islands to the continents. At the end of the last ice age, sea levels started to rise at unprecedented rates, leading to coastal retreat, drowning of land bridges and contraction of island areas. Although a growing number of studies take historical coastline dynamics into consideration, they are mostly based on past global sea‐level stands and present‐day water depths and neglect the influence of global geophysical changes on historical coastline positions. Here, we present a novel geophysically corrected global historical coastline position raster for the period from 26 ka to the present. This coastline raster allows, for the first time, calculation of global and regional coastline retreat rates and land loss rates. Additionally, we produced, per time step, 53 shelf sea rasters to present shelf sea positions and to calculate the shelf sea expansion rates. These metrics are essential to assess the role of isolation and connectivity in shaping marine and insular biodiversity patterns and evolutionary signatures within species and species assemblages. Main types of variables contained: The coastline age raster contains cells with ages in thousands of years before present (bp ), representing the time since the coastline was positioned in the raster cells, for the period between 26 ka and the present. A total of 53 shelf sea rasters (sea levels <140 m) are presented, showing the extent of land (1), shelf sea (0) and deep sea (NULL) per time step of 0.5 kyr from 26 ka to the present. Spatial location and grain: The coastline age raster and shelf sea rasters have a global representation. The spatial resolution is scaled to 120 arcsec (0.333° × 0.333°), implying cells of c . 3, 704 m around the equator, 3, 207 m around the tropics (±30°) and 1, 853 m in the temperate zone (±60°). Time period and temporal resolution: The coastline age raster shows the age of coastline positions since the onset of the LGM 26 ka, with time steps of 0.5 kyr. The 53 shelf sea rasters show, for each time step of 0.5 kyr, the position of the shelf seas (seas shallower than 140 m) and the extent of land. Level of measurement: Both the coastline age raster and the 53 shelf sea rasters are provided as TIFF files with spatial reference system WGS84 (SRID 4326). The values of the coastline age raster per grid cell correspond to the most recent coastline position (in steps of 0.5 kyr). Values range from 0 (0 ka, i.e., present day) to 260 (26 ka) in bins of 5 (0.5 kyr). A value of "no data" is ascribed to pixels that have remained below sea level since 26 ka. Software format: All data processing was done using the R programming language.